2015
DOI: 10.1039/c4ta06551d
|View full text |Cite
|
Sign up to set email alerts
|

Efficient hydrogen/oxygen evolution and photocatalytic dye degradation and reduction of aqueous Cr(vi) by surfactant free hydrophilic Cu2ZnSnS4 nanoparticles

Abstract: Use of hydrophilic Cu2ZnSnS4 nanoparticles as a multifunctional highly active heterogeneous catalyst: electrocatalytic water splitting, photocatalytic dye degradation and reduction of aqueous Cr(vi).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(58 citation statements)
references
References 43 publications
(66 reference statements)
0
54
0
Order By: Relevance
“…Also, Cu 2 FeSnS 4 (CFTS) and CZTSeS nanofibers were fabricated by our group for the first time . In previous studies, photocatalytic hydrogen evolution has been reported for CZTS nanoplates and nanocrystals . However, there has been only one report on the application of CZTS material as an H 2 ‐evolution electrocatalyst.…”
Section: Figurementioning
confidence: 74%
“…Also, Cu 2 FeSnS 4 (CFTS) and CZTSeS nanofibers were fabricated by our group for the first time . In previous studies, photocatalytic hydrogen evolution has been reported for CZTS nanoplates and nanocrystals . However, there has been only one report on the application of CZTS material as an H 2 ‐evolution electrocatalyst.…”
Section: Figurementioning
confidence: 74%
“…[5,38] This shift can be attributed also to the removal of someb romine atoms from EY and the possible formation of fluorescein-likes pecies. [5,38] This shift can be attributed also to the removal of someb romine atoms from EY and the possible formation of fluorescein-likes pecies.…”
Section: Photocatalytic Hydrogen Evolution By Cxts Nanofibersmentioning
confidence: 96%
“…[5,38] This shift can be attributed also to the removal of someb romine atoms from EY and the possible formation of fluorescein-likes pecies. [5] The differences between the HER rates of the nanofibersc ould be ascribed to the conduction-band (CB) levels. These resultsc omply with the hydrogen production rates of the nanofibers.…”
Section: Photocatalytic Hydrogen Evolution By Cxts Nanofibersmentioning
confidence: 96%
“…Data on photocatalytic degradation of Methylene Blue in the presence of kesterite Cu2ZnSnS4 can be found in recent literature [45][46][47][48]. However, the photocatalytic activity of the synthesized stannite Cu2FeSnS4 sample is here studied for the first time.…”
Section: Photocatalytic Activitymentioning
confidence: 99%